2011
DOI: 10.1162/jocn.2011.21610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooperating and Conflicting Prosody in Spoken English Garden Path Sentences: ERP Evidence for the Boundary Deletion Hypothesis

Abstract: Abstract■ In reading, a comma in the wrong place can cause more severe misunderstandings than the lack of a required comma. Here, we used ERPs to demonstrate that a similar effect holds for prosodic boundaries in spoken language. Participants judged the acceptability of temporarily ambiguous English "garden path" sentences whose prosodic boundaries were either in line or in conflict with the actual syntactic structure. Sentences with incongruent boundaries were accepted less than those with missing boundaries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
143
4
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(175 citation statements)
references
References 49 publications
(97 reference statements)
23
143
4
5
Order By: Relevance
“…These studies have demonstrated that IC bias information is influential in pronoun resolution prior to referential disambiguation downstream and therefore may play a predictive role regarding the pronoun's referent. Prosodic information is also often available prior to lexical disambiguating information in referential ambiguities (Ito & Speer, 2008;Weber et al, 2006) as well as structural ambiguities (Pauker, Itzhak, Baum, & Steinhauer, 2011;Steinhauer, Alter, & Friederici, 1999), and can potentially interact with IC bias information in order to improve processing efficiency. Prosodic information has previously been shown to play a facilitative role when interacting with structural biases in the context of parsing ambiguities (Itzhak, Pauker, Drury, Baum, & Steinhauer, 2010).…”
Section: Implicit Causality Biasesmentioning
confidence: 99%
“…These studies have demonstrated that IC bias information is influential in pronoun resolution prior to referential disambiguation downstream and therefore may play a predictive role regarding the pronoun's referent. Prosodic information is also often available prior to lexical disambiguating information in referential ambiguities (Ito & Speer, 2008;Weber et al, 2006) as well as structural ambiguities (Pauker, Itzhak, Baum, & Steinhauer, 2011;Steinhauer, Alter, & Friederici, 1999), and can potentially interact with IC bias information in order to improve processing efficiency. Prosodic information has previously been shown to play a facilitative role when interacting with structural biases in the context of parsing ambiguities (Itzhak, Pauker, Drury, Baum, & Steinhauer, 2010).…”
Section: Implicit Causality Biasesmentioning
confidence: 99%
“…The language CPS has been elicited at the boundary onset (Kerkhofs et al, 2007;Pauker et al, 2011), and the music component at the boundary offset. These latency differences have been accounted for by the fact that speech provides more and earlier boundary cues than music (Knoesche et al, 2005;Neuhaus et al, 2006).…”
Section: Implications For Shared Resources Hypothesesmentioning
confidence: 99%
“…An important distinction to note is that Honbolygo et al (2016) found increased processing for misleading prosody (reversing the intonation contour of the embedded clause), whereas the experimental sentences in the study 3 contain an absence of, rather than misleading, prosodic information. Pauker et al (2011) found that misleading prosody, where a superfluous prosodic boundary needed to be deleted for the listener to comprehend the spoken sentence, led to increased syntactic processing, as evidenced by a larger P600 waveform than for sentences presented without prosodic information. In other words, the absence of prosody in spoken sentences, where listeners needed to supply their own prosody led to syntactic revision, that was less costly than mentally deleting misleading prosodic boundaries.…”
Section: Syntactically Incorrectmentioning
confidence: 97%
“…Listeners use prosodic information to assist comprehension 20 of utterances including resolution of ambiguities (Kjelgaard & Speer, 1999). Further support for the rapid integration of prosody into spoken language is provided by electroencephalography (EEG) studies, where the Closure Positive Shift (CPS) is elicited in response to an intonational prosodic boundary, prior to syntactic processing occurring (Pauker, Itzhak, Baum, & Steinhauer, 2011;Steinhauer & Friederici, 2001). …”
Section: Summary: Prosody and Its Role In Spoken Language Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation